(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Concerns about the state of the environment in the modern day are directly driving an upsurge in the production and distribution of electric automobiles. In 2018, a significant infrastructural change took place in how manufacturers in India perceived electric vehicles. As a result, this thesis aims to investigate the factors that influence the level of commercial success achieved by electric cars in Hyderabad, as well as the customers’ intentions towards the purchase of electric vehicles. This research will use a variety of research approaches in order to comprehend the client purchase intention about electric automobiles. First, we will carry out the research using the quantitative approach